ANALYSIS OF HISTAMIN CONTENT IN LOIN TUNA (Thunnus maccoyii) In Denpasar, Bali - Siluh Putu Sri Dia Utari; Resti Nurmala Dewi; Ferlina Febrianti (Berkala Perikanan Terubuk, 2022)
Fish is a fishery resource that has very important economic value. One of the fishery commodities in Indonesia which is produced and exported in large quantities is bluefin tuna (Thunnus maccoyii). The high protein content causes tuna to be easily damaged if it is not immediately processed and stored at high ambient temperatures and can cause histamine. Histamine is a compound derived from the amino acid histidine which is formed due to the action of bacteria that have decarboxylase enzymes. The formation of histamine is influenced by several factors, including temperature and pH. The purpose of this study was to identify histamine content in raw materials and final products of bluefin tuna (Thunnus maccoyii) loin form. This test uses the ELISA (Enzyme Linked Immunosorbent Assay) method with VERATOX media (Veratox Quantitative Histamine Test Neogen). Histamine testing was carried out for approximately 5 days using 2 repetitions for both raw materials and frozen tuna loin products. The histamine content in raw materials and final products of frozen tuna loin does not exceed the SNI 4104:2015 standard, which is 100 ppm. The average histamine test result for raw tuna loin was 0.52 ppm and the average histamine test result for the final product was 0.96 ppm.